Artificial intelligence and global society impact and practices - Kumar, Puneet (Assistant professor); Jain, Vinod Kumar; Kumar, Dharminder (Boca Raton : Chapman & Hall/CRC, 2021)
In the constant battle between human intelligence and machine intelligence, machines are close to surpassing human intelligence. The unrestrained use of digital technologies in automating processes is one of the prime advantages of the third industrial revolution. As a result, all developed and developing nations have started to digitalize mundane tasks. Thus, digital technologies for information and communication technologies (ICT) have achieved high market space in terms of infrastructure building, employment generation, education sector reforms, funds mobilization, electronic governance, hardware manufacturing, software development, etc. Hence, it is evident that every segment of society has been penetrated by ICT or digitalization. This book attempts to spotlight areas where AI is thriving. FEATURES Impact of digitalization and AI on governance Novel AI practices being followed across the global community in security, healthcare, crime prevention and detection, education, agriculture, sensor networks, etc. Innovative techniques that can be adopted to ensure better quality and better delivery of services to the society Avenues for further research by the research community and student fraternity This book is a guide for university students (especially those from technical backgrounds), industries, NGOs, and policy makers.
OCLC-licensed vendor bibliographic record.
Keywords: Artificial intelligence -- Social aspects; Automation -- Social aspects; Sustainable development -- Technological innovations; COMPUTERS / Artificial Intelligence; COMPUTERS / Database Management / Data Mining; COMPUTERS / Machine Theory